A method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion

By preparing a 3D polymer nanochannel membrane and using sulfonated polyether ether ketone for ion exchange with column aromatic hydrocarbons, the problems of insufficient mass transfer and high membrane resistance in the osmotic energy conversion in the prior art are solved, high selectivity and high conductivity are achieved, and energy conversion efficiency is improved.

CN118987996BActive Publication Date: 2025-04-18TIANJIN POLYTECHNIC UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411384583.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-04-18
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing ion exchange membranes have problems such as insufficient mass transfer, high membrane resistance and low energy conversion efficiency in the permeability conversion, making it difficult to achieve high selectivity and high conductivity.

Method used

By preparing a 3D polymer nanochannel membrane, ion exchange is performed with sulfonated polyether ether ketone and column aromatic hydrocarbons to form a charged surface and high surfactivity to enhance cation transport.

Benefits of technology

It has achieved improved the utilization rate of permeability and the mechanical properties of the membrane, enhanced cation transmission, and energy conversion efficiency of nearly 50%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118987996B_ABST
    Figure CN118987996B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ion exchange membranes, and provides a preparation method of a 3D polymer nanochannel membrane for osmotic energy conversion, comprising: in a nitrogen environment, dissolving 1,4-dimethoxybenzene and paraformaldehyde in 1,2-dichloroethane, and then adding a first catalyst to react to obtain a first precipitate; dissolving the first precipitate in dichloromethane, and then adding a second catalyst to react to obtain a second precipitate; dissolving the second precipitate and potassium carbonate in acetonitrile, and then injecting ethyl bromoacetate to react to obtain a third precipitate; dissolving the third precipitate in tetrahydrofuran, and then adding a NaOH solution to react to obtain a fourth precipitate; dissolving the fourth precipitate, 2,5-diaminobenzenesulfonic acid, EDC and DMAP in DMF to react to obtain a fifth precipitate; dissolving sulfonated polyetheretherketone and the fifth precipitate in N,N-dimethylformamide to obtain a second liquid, and coating the second liquid on a stripping plate to obtain a channel membrane, so as to enhance the ion selectivity of the channel membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ion exchange membranes, and in particular to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion. Background Art

[0002] Currently, the total amount of osmotic energy available worldwide is estimated to be approximately 1 TW. Compared to other energy sources such as wind and solar, osmotic energy also has the advantage of not being subject to daily variations. Membrane-based reverse electrodialysis is a key technology for capturing this blue energy. Osmotic energy conversion is achieved through selective transmembrane ion diffusion through a charged membrane under a concentration gradient. Ion exchange membranes have long been the center of research on osmotic energy conversion by reverse electrodialysis because of their easy access, large surface area, and high ion selectivity. However, commonly used ion exchange membranes have several limitations, such as insufficient mass transfer and high membrane resistance, resulting in economically unfeasible power densities <2.2 Wm -2 . In addition, the charge polarization occurring at the membrane-solution interface seriously impairs ion transport and reduces energy conversion efficiency. The energy conversion efficiency mainly depends on the ion selectivity of ion-selective membranes, including traditional ion exchange membranes and emerging nanochannel membranes. In this context, further development to approach or even reach a conversion efficiency of 50% is another major challenge. An ideal membrane should have high selectivity and ion conductivity, which requires high ion permeability and low resistance. Increasing the charge density of the membrane and constructing relatively large channels are important ways to promote ion transport across the membrane. Sulfonated polyetheretherketone (SPEEK) consists of a rigid hydrophobic aromatic main chain and a hydrophilic sulfonated side group (-SO3H) directly bonded to the benzene ring. The low flexibility of the polymer main chain and the small distance between the main chain and the side group are not conducive to the formation of a typical hydrophobic-hydrophilic nanophase separation structure, resulting in poor continuity of the ion conduction domain and relatively low conductivity. Although increasing the degree of sulfonation of SPEEK can improve the conductivity of ions, it significantly reduces the selectivity of ions. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the related art. To this end, the present invention provides a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion to enhance the ion selectivity of the channel membrane.

[0004] The present invention provides a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion, comprising the following steps:

[0005] S1: Under a nitrogen environment, 1,2-dichloroethane is added to 1,4-dimethoxybenzene and polyformaldehyde to dissolve them, and then a first catalyst is added. After the reaction is completed, methanol is added to obtain a first precipitate;

[0006] S2: Under a nitrogen environment, dichloromethane is added to the first precipitate to dissolve it, and then a second catalyst is added to react. After the reaction is completed, the reaction solution is poured into ice water to obtain a second precipitate;

[0007] S3: under a nitrogen environment, acetonitrile is added to the second precipitate and potassium carbonate to dissolve them, and then ethyl bromoacetate is injected to react, and after the reaction is completed, a third precipitate is obtained;

[0008] S4: dissolving the third precipitate with tetrahydrofuran, adding NaOH solution, heating for reaction, and performing treatment after the reaction is completed to obtain a fourth precipitate;

[0009] S5: Under a nitrogen environment, using N,N-dimethylformamide to dissolve the fourth precipitate, 2,5-diaminobenzenesulfonic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 4-dimethylaminopyridine, and then reacting under heating conditions to obtain a fifth precipitate;

[0010] S6: Dissolving sulfonated polyetheretherketone with N,N-dimethylformamide to form a first liquid, adding the fifth precipitate to the first liquid to obtain a second liquid, coating the second liquid on a release template, and evaporating the solvent to obtain a 3D polymer nanochannel membrane.

[0011] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, in step S1, the first catalyst includes boron trifluoride ethyl ether; the molar ratio of the 1,4-dimethoxybenzene to the polyformaldehyde is 1: (3-6); the molar ratio of the 1,4-dimethoxybenzene to the boron trifluoride ethyl ether is 1: (1-3).

[0012] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, in step S2, the second catalyst includes boron tribromide, and the molar ratio of the first precipitate to the boron tribromide is 1:(0.3~0.5).

[0013] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, in step S3, the molar ratio of the second precipitate to the potassium carbonate is 1: (80-90); the molar ratio of the second precipitate to the ethyl bromoacetate is 1: (20-30).

[0014] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, in step S4, the NaOH solution is a 20% NaOH solution;

[0015] The molar ratio of the third precipitate to the sodium ions in the NaOH solution is 1:(150-200).

[0016] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, in step S5, the molar ratio of the fourth precipitate to the 2,5-diaminobenzenesulfonic acid is 1: (2-3); the molar ratio of the fourth precipitate to the 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 1: (8-12); the molar ratio of the fourth precipitate to the 4-dimethylaminopyridine is 1: (0.5-1).

[0017] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, obtaining the first precipitate in step S1 also includes the following steps: after adding methanol, stopping the reaction, precipitating a crude product of the first precipitate, collecting the crude product of the first precipitate by suction filtration, and separating and purifying the crude product of the first precipitate by silica gel chromatography to obtain a first precipitate.

[0018] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, obtaining the second precipitate in step S2 also includes the following steps: after adding into ice water, the reaction is stopped, a crude product of the second precipitate is precipitated, the crude product of the second precipitate is collected by suction filtration, the crude product of the second precipitate is repeatedly washed with 0.5 mol / L HCl solution and dichloromethane, and the precipitate is dried to obtain a second precipitate.

[0019] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, obtaining the third precipitate in step S3 also includes the following steps: using dichloromethane to dissolve the crude product of the third precipitate, filtering to obtain a third liquid, spinning the liquid to obtain the first product, then dissolving the first product with dichloromethane to obtain a fourth liquid, and adding methanol to the second liquid to obtain a third precipitate.

[0020] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, the heating temperature range in step S4 is 70-90° C.; and the heating temperature range in step S5 is 80-100° C.

[0021] The above one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects:

[0022] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion according to an embodiment of the present invention, a cavity structure of columnar aromatics is formed through multiple steps of preparation, and ion exchange is carried out between sulfonated polyetheretherketone and columnar aromatics to form a charged surface and high surface activity, thereby achieving enhanced cation transport and improving the utilization rate of osmotic energy.

[0023] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 This is the morphology of the SPEEK / SPP[5]-x composite membrane prepared in Example 1 provided by the present invention.

[0026] Figure 2 is the thickness of the SPEEK / SPP[5]-x composite film prepared in Example 1 provided by the present invention.

[0027] Figure 3 3 is the stress-strain curve of the SPEEK / SPP[5]-x composite film prepared in Example 1 provided by the present invention.

[0028] FIG. 4 ( a ) shows the annihilation time of positrons of different diameters and the lifetime value intensity in the SPEEK film and the SPEEK / SPP[5]-x composite film in Example 1 provided by the present invention.

[0029] FIG4( b ) shows the change of the Zeta potential of the SPEEK / SPP[5]-x composite membrane in the pH range of 2 to 9 in Example 1 provided by the present invention.

[0030] FIG5( a ) is a comparison diagram of the relationship between the output power and the electrons in the SPEEK / SPP[5]-x composite membrane and the SPEEK / SPP[1] composite membrane in Example 1 provided by the present invention.

[0031] FIG5( b ) is a comparison diagram of the relationship between the output power and the electrons in the SPEEK / SPP[5]-x composite membrane at different concentration gradients in Example 1 provided by the present invention.

[0032] Figure 6 This is the carbon NMR spectrum of SPP[5] synthesized in Example 1 provided by the present invention. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The following embodiments are used to illustrate the present invention, but cannot be used to limit the scope of the present invention.

[0034] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0035] In the following examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0036] The present invention provides a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion, comprising the following steps:

[0037] S1: Under a nitrogen environment, 1,2-dichloroethane is added to 1,4-dimethoxybenzene and polyformaldehyde to dissolve them, and then a first catalyst is added. After the reaction is completed, methanol is added to obtain a first precipitate;

[0038] S2: Under a nitrogen environment, dichloromethane is added to the first precipitate to dissolve it, and then a second catalyst is added to react. After the reaction is completed, the reaction solution is poured into ice water to obtain a second precipitate;

[0039] S3: under a nitrogen environment, acetonitrile is added to the second precipitate and potassium carbonate to dissolve them, and then ethyl bromoacetate is injected to react, and after the reaction is completed, a third precipitate is obtained;

[0040] S4: dissolving the third precipitate with tetrahydrofuran, adding NaOH solution, heating for reaction, and performing treatment after the reaction is completed to obtain a fourth precipitate;

[0041] S5: Under a nitrogen environment, using N,N-dimethylformamide to dissolve the fourth precipitate, 2,5-diaminobenzenesulfonic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 4-dimethylaminopyridine, and then reacting under heating conditions to obtain a fifth precipitate;

[0042] S6: Dissolving sulfonated polyetheretherketone with N,N-dimethylformamide to form a first liquid, adding the fifth precipitate to the first liquid to obtain a second liquid, coating the second liquid on a release template, and evaporating the solvent to obtain a 3D polymer nanochannel membrane.

[0043] In this embodiment, the cavity structure of pillar aromatic hydrocarbon is formed through multiple steps of preparation, and sulfonated polyetheretherketone is used to carry out ion exchange with pillar aromatic hydrocarbon to form a charged surface and high surface activity, thereby achieving enhanced cation transport and improving the utilization rate of osmotic energy.

[0044] According to some embodiments of the present invention, in step S1, the reaction is carried out at room temperature, 1,2-dichloroethane is added to 1,4-dimethoxybenzene and polyformaldehyde for dissolution, and the first catalyst is added after stirring for 1 hour. After adding the first catalyst, the reaction is stirred at room temperature, and thin layer chromatography (TCL) is used for detection to determine whether the reaction is complete.

[0045] According to some embodiments of the present invention, the first precipitate is a white powder of methoxy-pillar[5]arene (P[5]) having the structural formula:

[0046] .

[0047] According to some embodiments of the present invention, in step S2, the reaction is stirred for 72 hours, and the second precipitate is a white solid. The second precipitate is stored under nitrogen conditions. The second precipitate is P[5]-OH, and its structural formula is:

[0048] .

[0049] According to some embodiments of the present invention, in step S3, the second precipitate and potassium carbonate are placed in a reaction bottle equipped with a condenser reflux tube for reaction at a temperature of 70 to 90° C. for 10 hours. The third precipitate is a white solid. The third precipitate is P[5]-COOEt, and its structural formula is:

[0050] .

[0051] According to some embodiments of the present invention, in step S4, the third precipitate and potassium carbonate are weighed and placed in a reaction bottle equipped with a condensing reflux tube, and after nitrogen is pumped, 100 mL of acetonitrile is injected and added, and stirred at a temperature of 70 to 90 ° C. After the solvent refluxes, ethyl bromoacetate is slowly injected and reacted overnight. After the reaction is completed, it is allowed to stand and cool, the precipitate is repeatedly washed with dichloromethane, the liquid is filtered and collected, the liquid is spin-dried and then dissolved with dichloromethane, methanol is added for crystallization, the solid is filtered and collected, and vacuum drying is performed to obtain a fourth precipitate as a white solid.

[0052] According to some embodiments of the present invention, the fourth precipitate is P[5]-COOH, which has the structural formula:

[0053] .

[0054] According to some embodiments of the present invention, in step S5, a fourth precipitate, 2,5-diaminobenzenesulfonic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 4-dimethylaminopyridine (DMAP) are added to a reaction bottle equipped with a condenser reflux tube, N,N-dimethylformamide (DMF) is injected into the reaction bottle, and the reaction is stirred at a temperature of 80-100° C. for 96 hours. After the reaction is completed, the reaction is allowed to stand and cool, and the precipitate is collected by filtration. The precipitate is repeatedly washed with ethanol and water, and vacuum dried to obtain a purple solid fifth precipitate. The fifth precipitate is a P[5]-SO3H polymer molecule (SPP[5]). The quantitative 13 The C NMR spectrum confirmed the composition of SPP[5]. Through accurate integration, the possible structural formula of the cross-linked polymer SPP[5] included:

[0055] , and .

[0056] According to some embodiments of the present invention, the obtained product is subjected to Fourier transform infrared spectroscopy analysis. Compared with P[5]-COOH, the vibration absorption peak of C=O on P[5]-SO3H increases from 1736 cm -1 Move to 1665cm -1 , and compared with 2,5-diaminobenzenesulfonic acid (DTS-SO3H) at 3410 cm -1 The disappearance of the amino vibration peak at 1080cm -1 The appearance of the sulfonate vibration peak at 400 nm indicated that a cross-linking reaction occurred between the carboxyl group of P[5]-COOH and the amino group of DTS-SO3H, resulting in the synthesis of the P[5]-SO3H polymer molecule (SPP[5]).

[0057] According to some embodiments of the present invention, in step S6, the preparation of sulfonated polyetheretherketone: before the reaction, the raw material polyetheretherketone (PEEK) is placed in an oven and dried at 70-90°C for 15 hours to fully remove the moisture in the raw material to avoid its influence on the sulfonation reaction. 1g PEEK is slowly added to 20mL concentrated sulfuric acid while stirring at low temperature. After PEEK is completely dissolved, it is heated to 40-60°C to start the reaction. After stirring for 8 hours, the reaction solution is poured into ice water to generate a white fibrous precipitate. The precipitate is washed until the washing liquid is neutral, and the resulting precipitate is dried at 50-70°C to finally obtain a yellow-white solid sulfonated polyetheretherketone (SPEEK).

[0058] According to some embodiments of the present invention, in step S6, the temperature range of the low temperature condition is 0-5°C.

[0059] According to some embodiments of the present invention, in step S6, 30 mg of SPEEK is weighed and dissolved in 0.3 mL of DMF to form a polymer solution, and then SPP[5] is added and stirred evenly to prepare a casting solution. The casting solution is coated on a glass plate and placed in a 60°C vacuum box to completely evaporate the solvent, and then immersed in water to separate the composite film from the glass plate to obtain a 3D polymer nanochannel membrane (SPEEK / SPP[5]-x), which is represented by SPEEK / SPP[5]-x, where "x" represents the doping level of SPP[5] (0%, 5%, 20%, 30% and 40%). The chemical composition of the 3D polymer nanochannel membrane (3D INMs) was determined by XPS spectroscopy.

[0060] The above steps were used to prepare SPEEK membranes without adding SPP[5], SPEEK / SPP[5]-5% composite membranes with adding 5%wt SPP[5], SPEEK / SPP[5]-20% composite membranes with adding 20%wt SPP[5], SPEEK / SPP[5]-30% composite membranes with adding 30%wt SPP[5], and SPEEK / SPP[5]-40% composite membranes with adding 40%wt SPP[5] polymer.

[0061] According to some preferred embodiments of the present invention, the size of the SPEEK / SPP[5]-x composite membrane is π×32 m 2 .

[0062] Figure 1 This is the morphology of the SPEEK / SPP[5]-x composite membrane prepared in Example 1 provided by the present invention. Figure 2 is the thickness of the SPEEK / SPP[5]-x composite film prepared in Example 1 provided by the present invention.

[0063] According to some embodiments of the present invention, Figure 1 As shown in the figure, the morphology of the SPEEK / SPP[5]-x ((a) SPEEK / SPP[5]-5%, (b) SPEEK / SPP[5]-20%, (c) SPEEK / SPP[5]-30%, (d) SPEEK / SPP[5]-40%) composite membranes was studied by field emission scanning electron microscopy (FE-SEM). The membrane surface showed a dense structure, and there was no significant difference except for SPEEK / SPP[5]-40%.

[0064] According to some preferred embodiments of the present invention, Figure 2 As shown, cross-sectional SEM images show that the thicknesses of the SPEEK / SPP[5]-x ((a) SPEEK / SPP[5]-0%, (b) SPEEK / SPP[5]-5%, (c) SPEEK / SPP[5]-20%, (d) SPEEK / SPP[5]-30%) composite films are 15.4 μm, 15.8 μm, 15.5 μm, and 16.3 μm, respectively.

[0065] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, in step S1, the first catalyst includes boron trifluoride ethyl ether; the molar ratio of the 1,4-dimethoxybenzene to the polyformaldehyde is 1: (3-6); the molar ratio of the 1,4-dimethoxybenzene to the boron trifluoride ethyl ether is 1: (1-3).

[0066] According to some preferred embodiments of the present disclosure, the molar ratio of the 1,4-dimethoxybenzene to the paraformaldehyde is 1:5; the molar ratio of the 1,4-dimethoxybenzene to the boron trifluoride etherate is 1:1.06.

[0067] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, in step S2, the second catalyst includes boron tribromide, and the molar ratio of the first precipitate to the boron tribromide is 1:(0.3~0.5).

[0068] According to some preferred embodiments of the present disclosure, the molar ratio of the first precipitate to the boron tribromide is 1:0.4. According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, in step S3, the molar ratio of the second precipitate to the potassium carbonate is 1:(80-90); the molar ratio of the second precipitate to the ethyl bromoacetate is 1:(20-30).

[0069] According to some preferred embodiments of the present disclosure, the molar ratio of the second precipitate to the potassium carbonate is 1:66; the molar ratio of the second precipitate to the ethyl bromoacetate is 1:27. According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, in step S4, the NaOH solution uses a 20% NaOH solution; the molar ratio of the third precipitate to the sodium ions in the NaOH solution is 1:(150~200).

[0070] According to some preferred embodiments of the present disclosure, the molar ratio of the third precipitate to the sodium ions in the NaOH solution is 1:175.

[0071] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, in step S5, the molar ratio of the fourth precipitate to the 2,5-diaminobenzenesulfonic acid is 1: (2-3); the molar ratio of the fourth precipitate to the 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 1: (8-12); the molar ratio of the fourth precipitate to the 4-dimethylaminopyridine is 1: (0.5-1).

[0072] According to some preferred embodiments of the present disclosure, the molar ratio of the fourth precipitate to the 2,5-diaminobenzenesulfonic acid is 1:3; the molar ratio of the fourth precipitate to the 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 1:10.5; the molar ratio of the fourth precipitate to the 4-dimethylaminopyridine is 1:0.53. According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, obtaining the first precipitate in step S1 also includes the following steps: after adding methanol, the reaction is stopped, and a crude product of the first precipitate is precipitated, the crude product of the first precipitate is collected by suction filtration, and the crude product of the first precipitate is separated and purified by silica gel chromatography to obtain the first precipitate.

[0073] According to some embodiments of the present invention, the molar ratio of dichloromethane to petroleum ether in the silica gel is 1:1.

[0074] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, obtaining the second precipitate in step S2 also includes the following steps: after adding ice water, the reaction is stopped, a crude product of the second precipitate is precipitated, the crude product of the second precipitate is collected by suction filtration, the crude product of the second precipitate is repeatedly washed with 0.5 mol / L HCl solution and dichloromethane, and the precipitate is dried to obtain a second precipitate.

[0075] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, obtaining the third precipitate in step S3 also includes the following steps: using dichloromethane to dissolve the crude product of the third precipitate, filtering to obtain a third liquid, spinning the liquid to obtain the first product, then dissolving the first product with dichloromethane to obtain a fourth liquid, and adding methanol to the second liquid to obtain a third precipitate.

[0076] According to a method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion provided by the present invention, the heating temperature range in step S4 is 70-90° C.; and the heating temperature range in step S5 is 80-100° C.

[0077] The technical solution of the present invention is further explained below in conjunction with a specific embodiment. It should be noted that this specific embodiment is only for those skilled in the art to better understand the technical solution of the present invention, and should not be regarded as an unreasonable limitation on the protection scope of the present invention.

[0078] Embodiment 1

[0079] Step 1: Synthesis of SPP[5]

[0080] Step 11: Synthesis of P[5]: Weigh 1,4-dimethoxybenzene (5 g, 36.19 mmol) and paraformaldehyde (5.43 g, 181 mmol) into a reaction bottle, evacuate with nitrogen, inject 100 mL of 1,2-dichloroethane, and stir at 25°C for 1 h. Slowly add boron trifluoride ether (4.72 mL, 38 mmol) under nitrogen protection, stir and react at 25°C, confirm the completion of the reaction by TCL, add methanol to precipitate the product, collect the precipitate by suction, and separate and purify the crude product by silica gel chromatography (dichloromethane / petroleum ether 1:1) to obtain white powder P[5] (yield 3.81 g, yield 70.53%).

[0081] Step 12: Synthesis of P[5]-OH: Weigh P[5] (3 g, 4 mmol) obtained by the above reaction and put it into a reaction bottle equipped with a constant pressure dropping funnel, pump nitrogen, inject 100 mL of dichloromethane, slowly drop 10 mL of dichloromethane and 13.5 mL of boron tribromide through the constant pressure dropping funnel, and stir to react for 72 hours. After the reaction is completed, pour the reaction solution into ice water to stop the reaction. A precipitate appears, collect the precipitate by suction filtration, wash the precipitate repeatedly with 0.5 mol / L HCl and dichloromethane three times, and vacuum dry to obtain P[5]-OH as a white solid (yield 2.14 g, yield 87.80%), and store the product under nitrogen conditions.

[0082] Step 13: Synthesis of P[5]-COOEt: Weigh the above-obtained P[5]-OH (2 g, 3.3 mmol) and potassium carbonate (30 g, 217.1 mmol) and place them in a reaction bottle equipped with a condenser reflux tube. After pumping nitrogen, inject 100 mL of acetonitrile and stir at 80°C. After the solvent refluxes, slowly inject ethyl bromoacetate (10 mL, 90.42 mmol) and react overnight. After the reaction is completed, stand and cool, wash the precipitate repeatedly with dichloromethane, filter and collect the liquid, spin dry the liquid and then dissolve it with dichloromethane, add methanol for crystallization, filter and collect the solid, and vacuum dry to obtain P[5]-COOEt as a white solid (yield 1.92 g, yield 39.53%).

[0083] Step 14: Synthesis of P[5]-COOH: P[5]-COOEt (1.92 g, 1.3 mmol) obtained in the above reaction was weighed into a reaction flask and dissolved in 60 mL of tetrahydrofuran. Subsequently, 30 mL of 20% NaOH solution was added and stirred at 80°C and heated to reflux. After reacting for 15 h, the mixture was allowed to stand and cool. The mixture was concentrated by rotary evaporation and diluted with water. Concentrated hydrochloric acid was added to precipitate the product. The precipitated product was collected by filtration, washed with deionized water several times, and dried in vacuo to obtain white powder P[5]-COOH (yield 1.32 g, yield 84.52%).

[0084] Step 15: Synthesis of SPP[5]: Add the obtained P[5]-COOH (1.13 g, 0.95 mmol) and 2,5-diaminobenzenesulfonic acid (0.5646 g, 3 mmol), EDC (2 g, 10 mmol), and DMAP (0.06 g, 0.5 mmol) into a reaction bottle equipped with a reflux tube, pump nitrogen, and inject 100 mL of DMF. Stir and react at 90°C for 96 hours. After the reaction is completed, let it stand and cool, filter and collect the precipitate, wash the precipitate repeatedly with ethanol and water, and vacuum dry to obtain a purple solid, namely SPP[5]. Figure 6 As shown, the successful synthesis of SPP[5] was confirmed by the image results of carbon NMR spectroscopy. 13 The composition of SPP[5] was determined by C NMR spectrum. Through accurate integration, the possible structure of the cross-linked polymer SPP[5] is as follows: Figure 6 shown.

[0085] The obtained product was subjected to Fourier transform infrared spectroscopy test. Compared with P[5]-COOH, the vibration absorption peak of C=O on P[5]-SO3H increased from 1736 cm -1 Move to 1665cm -1 , and compared with DTS-SO3H 3410cm -1 The disappearance of the amino vibration peak at 1080cm-1 The appearance of the sulfonate vibration peak at 440 nm indicated that a cross-linking reaction occurred between the carboxyl group of P[5]-COOH and the amino group of DTS-SO3H, resulting in the synthesis of SPP[5].

[0086] Step 2: Preparation of sulfonated polyetheretherketone

[0087] Before the reaction, the raw material PEEK was placed in an oven and dried at 80°C for 15 hours to fully remove the moisture in the raw material to avoid its influence on the sulfonation reaction. 1g of PEEK was slowly added to 20mL of concentrated sulfuric acid while stirring at low temperature. After PEEK was completely dissolved, it was heated to 50°C to start the reaction. After stirring for 8 hours, the reaction solution was poured into ice water to generate a white fibrous precipitate. The precipitate was washed until the washing liquid was neutral, and the obtained precipitate was dried at 60°C to finally obtain yellow-white solid SPEEK.

[0088] Step 3: Synthesis of P[1]-SO3H polymer molecule (SPP[1])

[0089] Step 31: Synthesis of P[1]-COOEt: Weigh hydroquinone (1.38 g, 0.0125 mmol) and potassium carbonate (30 g, 217.1 mmol) and place them in a reaction bottle equipped with a condenser reflux tube. After nitrogen is pumped in, 100 mL of acetonitrile is injected and stirred at 80°C. After the solvent refluxes, ethyl bromoacetate (10 mL, 90.42 mmol) is slowly injected and reacted overnight. After the reaction is completed, the mixture is allowed to stand and cool, and the precipitate is repeatedly washed with dichloromethane, and the liquid is collected by filtration. After the liquid is dried by spin drying, it is dissolved in dichloromethane again, methanol is added for crystallization, and the solid is collected by filtration. The white solid P[1]-COOEt (yield 1.5122 g, yield 42.9%) is obtained. In terms of molar ratio, hydroquinone: potassium carbonate: ethyl bromoacetate = 1:15~20:5~10.

[0090] Step 32: Synthesis of P[1]-COOH: P[1]-COOEt (1.2 g, 4.3 mmol) obtained in the above reaction was weighed and added to a reaction bottle, dissolved in 30 mL of tetrahydrofuran, and then 15 mL of 20% NaOH solution was added. The mixture was stirred at 80°C, heated to reflux, reacted for 15 h, allowed to stand and cooled, concentrated by rotary evaporation, diluted with water, and concentrated hydrochloric acid was added to precipitate the product. The precipitated product was collected by filtration, washed with deionized water for several times, and vacuum dried to obtain white powder P[1]-COOH (yield 0.8162 g, yield 83.99%). In terms of molar ratio, P[1]-COOEt: sodium hydroxide = 1:30~50.

[0091] Step 33: Synthesis of P[1]-SO3H polymer molecule (SPP[1])

[0092] Synthesis of P[1]-SO3H polymer molecule: P[1]-COOH (0.452 g, 2 mmol) obtained by the reaction, 2,5-diaminobenzenesulfonic acid (1.0332 g, 6 mmol), EDC (3.1048 g, 20 mmol), and DMAP (0.12 g, 1 mmol) were added to a reaction bottle equipped with a condenser reflux tube, and 100 mL of DMF was injected after nitrogen was pumped in. The reaction was stirred at 90°C for 96 hours. After the reaction was completed, the mixture was allowed to stand and cool, and the precipitate was collected by filtration. The precipitate was repeatedly washed with ethanol and water, and vacuum dried to obtain purple solid P[1]-SO3H. In terms of molar ratio, P[1]-COOH: 2,5-diaminobenzenesulfonic acid: EDC: DMAP = 1: 2~3: 8~12: 0.5~1.

[0093] Step 4: Preparation of SPEEK / SPP[5]-x composite membrane

[0094] In this experiment, the solution casting method was used to prepare SPEEK / SPP[5]-x composite membranes with different P[5]-SO3H contents.

[0095] 30 mg of SPEEK was weighed and dissolved in 0.3 mL of DMF to form a polymer solution. Subsequently, 30% wt P[5]-SO3H polymer was added and stirred evenly to prepare a casting solution. The casting solution was coated on a glass plate and placed in a 60°C vacuum oven to completely evaporate the solvent. The composite membrane was then immersed in water to separate from the glass plate to obtain a SPEEK / SPP[5]-30% composite membrane. SPEEK membrane, SPEEK / SPP[5]-5% composite membrane, SPEEK / SPP[5]-20% composite membrane, SPEEK / SPP[5]-30% composite membrane, SPEEK / SPP[5]-40% composite membrane and SPEEK / SPP[1]-30% composite membrane were prepared in the same manner.

[0096] The mechanical properties of membranes are crucial for their potential large-scale industrial applications as osmotic energy generators. Figure 3 As shown in the stress-strain curve of SPEEK / SPP[5]-x composite film, Young's modulus is the ratio of normal stress to normal strain. The Young's modulus can be compared by comparing the slope of the curve. Figure 3 It can be concluded that the slopes of SPEEK / SPP[5]-5%, SPEEK / SPP[5]-20% and SPEEK / SPP[5]-30% are all greater than SPEEK / SPP[5]-0%, that is, the Young's modulus of SPEEK / SPP[5]-x increases after the addition of SPP[5], and SPEEK / SPP[5]-x exhibits strong mechanical properties.

[0097] Among them, the toughness and Young's modulus of the SPEEK / SPP[5]-x composite film were calculated based on the stress-strain curve. Compared with the pure SPEEK film, the mechanical strength of the film was improved after doping with SPP[5]. The excellent mechanical properties were attributed to the strong hydrogen bonding interaction between SPEEK and P[5]-SO3H molecules.

[0098] Positron annihilation lifetime spectroscopy (PALS) further revealed the free volume change of the SPEEK / SPP[5]-x composite membrane and confirmed the change of the voids in the membrane. As shown in Figure 4 (a), the longer the positron annihilation lifetime (LT), the larger the free volume diameter (Diameter) of the membrane. Compared with the SPEEK membrane without SPP[5], the SPEEK / SPP[5]-x composite membrane provides a larger ion transport channel. In addition, as shown in Figure 4 (b), the change of the Zeta potential (Zetapotential) of the SPEEK / SPP[5]-x composite membrane in the pH range of 2~9 reflects that the SPEEK / SPP[5]-x composite membrane is negatively charged as a whole, and has a more obvious repulsion effect on highly negatively charged ions, and the anion retention rate is increased, which is beneficial to the transport of cations to achieve better anion and cation selectivity.

[0099] As shown in Figure 5(a) and Figure 5(b), the performance of the composite membrane was further evaluated using a custom-made osmotic energy generation device, which consists of two independent reservoirs, each containing a NaCl solution of different concentrations; the reservoirs are connected by a membrane, and ions can be transported through the membrane along the salinity gradient. The experiment was carried out under a 50-fold NaCl concentration gradient. The current I SC and open circuit voltage V OC The values ​​are 19.3μA and 145mV, respectively, and the membrane resistance is about 7.5KΩ. In comparison, the membrane resistance (External resistance) of the SPEEK membrane without SPP[5] is about 37.3KΩ, and the membrane resistance of the SPEEK membrane doped with 5% and 20% is 13.2KΩ and 10.3KΩ, respectively. It can be concluded that the SPEEK / SPP[5]-30% composite membrane is more conducive to cation transport. With the increase of doping level, when the content increases to 30%, the power density (Power density) of the membrane is the highest, calculated as Pmax=I 2 ×R L , where Pmax is the power density of the membrane, I is the current in the membrane, and R L is the membrane resistance. The calculated maximum power density of the SPEEK / SPP[5]-30% composite membrane is 19.3 W m -2 , exceeding the SPEEK / SPP[5]-5% composite film (10.9W m -2) and SPEEK / SPP[5]-20% composite membrane (15.8W m -2 ), which is due to the enhanced ion transport of the spatial structure of SPP. SPEEK / SPP[5]-30% corresponding to Na + The transmission number is 0.98, which is higher than that of other membranes and very close to the ideal transmission number ( t + =1). In addition, the ion transport behavior of SPEEK / SPP[5]-30% in different monovalent salt solutions was tested. The open circuit voltage (Voc) representing the ion selective transmembrane transport follows the trend of Na+>K+>Li+, and the results show that Na+ is rapidly transported in the 3D INMs nanochannels. In addition, it was found that the cation / anion selectivity of SPEEK / SPP[5]-30% follows the trend of Na + (0.98)>K + (0.89)>Li + Since the size of hydrated ions is larger than that of the nanochannel gate, dehydration behavior occurs when ions diffuse across the membrane.

[0100] A 3D polymer nanochannel membrane was designed by using sulfonated polyetheretherketone (SPEEK) and three-dimensional network sulfonated polypillar[5]arene (SPP[5]) for ion exchange, which was used for highly selective Na+ / Cl- transport and efficient salt gradient energy conversion. The 3D polymer chains stacked with negatively charged sulfonic acid groups formed cation-selective nanochannels, in which the sulfonic acid groups served as Na+ selective sites. Positron annihilation lifetime spectroscopy (PALS) found that SPP[5] doping changed the free volume and reconstructed the selective nanochannels with a channel size of less than 1 nm. Under a 50-fold salinity gradient, the 3D polymer nanochannel membranes (3D INMs) showed an ultra-high cation selectivity coefficient ( t + ) 0.98 and Na+ / Cl− selectivity 54.6. In salinity gradient energy harvesting, when the SPP[5] doping content was 30%, SPP[5] provided 19.3W m -2 In addition, the salinity gradient energy conversion efficiency is as high as 46.5%, which is closest to the upper limit of 50%.

[0101] The enhanced cation transport behavior is attributed to the cavity structure within the pillar aromatics, so a reference experiment was performed. First, as shown in Figure 5(a), the green line represents the output power of the SPEEK / SPP[1]-30% composite membrane, and the red line represents the output power of the SPEEK / SPP[5]-30% composite membrane. SPP[1] without a macrocyclic cavity was mixed with SPEEK using the same procedure. Compared with the SPEEK / SPP[1]-30% composite membrane, the SPEEK / SPP[5]-30% composite membrane had a higher Pmax. Figure 5 (b) evaluates the output power of the SPEEK / SPP[5]-30% composite membrane under different salinity gradients; 0.01M / 5M is the green line, representing the output power of the SPEEK / SPP[5]-30% composite membrane when the salinity gradient is 500 times; 0.01M / 0.5M is the yellow line, representing the output power of the SPEEK / SPP[5]-30% composite membrane when the salinity gradient is 50 times; 0.01M / 0.05M is the red line, representing the output power of the SPEEK / SPP[5]-30% composite membrane when the salinity gradient is 5 times. The increase in salinity gradient leads to higher power density, ranging from 0.22 (salinity gradient is 5 times) to 73.4 W m -2 (salinity gradient is 500 times). In addition, SPEEK / SPP[5]-30% exhibited ultra-high Na+ selectivity under a 50-fold NaCl salinity gradient, indicating high energy conversion efficiency. The corresponding efficiencies were calculated, and SPEEK / SPP[5]-30% showed the highest energy conversion efficiency of 46.1%. This energy conversion efficiency was most prominent under a 50-fold NaCl salinity gradient. In addition, SPEEK / SPP[5]-30% showed good stability over at least 8 cycles by continuously switching the current at plus or minus 1V and still remaining stable.

[0102] The rational introduction of macrocyclic compounds can form self-assembled nanochannel membranes with precise ion screening capabilities. The mechanism by which the nanochannels formed by SPP[5] and SPEEK chains can achieve high-speed cation transport comes from two aspects. First, the reversible hydrogen bonding interaction between the EDC group and the carboxylic acid group and the negatively charged sulfonic acid group on SPP[5] enables fast adsorption, large adsorption capacity and easy recycling. The flexibility and swellability of the cross-linked column[5] aromatic polymer structure as a filler allows all its adsorption sites to be fully in contact with the solution.

[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion, characterized in that: The following steps are involved: S1: Under a nitrogen environment, 1,2-dichloroethane is added to 1,4-dimethoxybenzene and polyformaldehyde to dissolve them, and then a first catalyst is added. After the reaction is completed, methanol is added to obtain a first precipitate; Wherein, the first catalyst comprises boron trifluoride etherate; The molar ratio of the 1,4-dimethoxybenzene to the paraformaldehyde is 1:(3-6); The molar ratio of the 1,4-dimethoxybenzene to the boron trifluoride ether is 1:(1-3); S2: Under a nitrogen environment, dichloromethane is added to the first precipitate to dissolve it, and then a second catalyst is added to react. After the reaction is completed, the reaction solution is poured into ice water to obtain a second precipitate; Wherein, the second catalyst comprises boron tribromide, and the molar ratio of the first precipitate to the boron tribromide is 1:(0.3-0.5); S3: under a nitrogen environment, acetonitrile is added to the second precipitate and potassium carbonate to dissolve them, and then ethyl bromoacetate is injected to react, and after the reaction is completed, a third precipitate is obtained; S4: After dissolving the third precipitate with tetrahydrofuran, adding NaOH solution, heating to react, after the reaction is completed, standing to cool, repeatedly washing the precipitate with dichloromethane, filtering to collect the liquid, spinning the liquid to dryness, then dissolving it with dichloromethane, adding methanol for crystallization, filtering to collect the solid, and vacuum drying to obtain a fourth precipitate as a white solid; S5: Under a nitrogen environment, using N,N-dimethylformamide to dissolve the fourth precipitate, 2,5-diaminobenzenesulfonic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 4-dimethylaminopyridine, and then reacting under heating conditions to obtain a fifth precipitate; S6: Dissolving sulfonated polyetheretherketone with N,N-dimethylformamide to form a first liquid, adding the fifth precipitate to the first liquid to obtain a second liquid, coating the second liquid on a release template, and evaporating the solvent to obtain a 3D polymer nanochannel membrane.

2. The method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion according to claim 1, characterized in that: In step S3, the molar ratio of the second precipitate to the potassium carbonate is 1:(80-90); The molar ratio of the second precipitate to the ethyl bromoacetate is 1:(20-30).

3. The method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion according to claim 1, characterized in that: In step S4, the NaOH solution is a 20% NaOH solution; The molar ratio of the third precipitate to the sodium ions in the NaOH solution is 1:(150-200).

4. The method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion according to claim 1, characterized in that: In step S5, the molar ratio of the fourth precipitate to the 2,5-diaminobenzenesulfonic acid is 1:(2-3); The molar ratio of the fourth precipitate to the 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 1:(8-12); The molar ratio of the fourth precipitate to the 4-dimethylaminopyridine is 1:(0.5-1).

5. The method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion according to claim 1, characterized in that: Obtaining the first precipitate in step S1 also includes the following steps: after adding methanol, the reaction is stopped to precipitate a crude product of the first precipitate, the crude product of the first precipitate is collected by suction filtration, and the crude product of the first precipitate is separated and purified by silica gel chromatography to obtain the first precipitate.

6. The method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion according to claim 1, characterized in that: Obtaining the second precipitate in step S2 also includes the following steps: after adding ice water, the reaction is stopped, a crude product of the second precipitate is precipitated, the crude product of the second precipitate is collected by suction filtration, the crude product of the second precipitate is repeatedly washed with 0.5 mol / L HCl solution and dichloromethane, and the precipitate is dried to obtain a second precipitate.

7. The method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion according to claim 1, characterized in that: Obtaining the third precipitate in step S3 also includes the following steps: using dichloromethane to dissolve the crude product of the third precipitate, filtering to obtain a third liquid, spinning the liquid to dryness to obtain the first product, then dissolving the first product with dichloromethane to obtain a fourth liquid, and adding methanol to the second liquid to obtain a third precipitate.

8. The method for preparing a 3D polymer nanochannel membrane for osmotic energy conversion according to claim 1, characterized in that: In step S4, the heating temperature ranges from 70 to 90°C; and in step S5, the heating temperature ranges from 80 to 100°C.

Citation Information

Patent Citations

  • Film material with ionic exchange performance and use thereof

    CN101264427A

  • Two-dimensional layered supermolecular skeleton structure nano separation membrane, and preparation method and application thereof in nano particle separation

    CN111203117A